Nominative Specificity of English Marketing Terminology - I. B. Rubert; T. S. Rosyanova; S. V. Kiselieva (Дискурс, 2020)
Introduction. The paper deals with the concepts of a term and terminology as they considered both in classical general theory of terminology and cognitive linguistics. The field of English economic terminology provides extensive material for the terminologists to develop and clarify theoretical guidelines helping to understand the nature of scientific and professional nominations that constitute the aim of presented reseach. The processes of term formation viewed through the cognitive approach are considered in connection with conceptualization and categorization and help to reveal the creative nominative models of marketers as it is seen vital within an antropocentric focus of linguistic studies.Methodology and sources. A general theory of terminology is based upon the approach in which the nature of concepts, conceptual relations, the relationships between terms and concepts and assigning terms to concepts are of prime importance. But in fact, terminology is closely linked to an activity carried out within the field of knowledge and thus it is inseparable from its social context and its obvious applications. Methods of cognitive analysis applied for the study of terminilogies are supposed to overcome contradictions of the previous century of terminology studies. English marketing terms under consideration were extracted from the professional dictionaries and handbooks. The thematic group chosen as the illustrative example is consumer terminological group.Results and discussion. Nominative originality of marketing terminology has been revealed within the idea of continually changing specific autonomous and self-sufficient consumer models reflected in micro-systems of terms nominating and verbalizing holistic concepts of the authors. Nomination of the typical individuals (customers) by the terms discussed in the presented paper reflects deep and various psychological characteristics of individuals. As it seems, all these parameters form the foundation of the professional domain of modern markets in accordance with the existing conceptual knowledge, verbalized by terms.Conclusion. The study is relevant since the research of conceptualization and categorization in the professional fields of knowledge seems to be an understudied area. The more interdisciplinary is the area of professional knowledge, the more integrated are specific features of terminological nomination, and the more sophisticated is the termformation used by the experts.